KATA SERAPAN BAHASA SASAK DARI BAHASA ARAB (ANALISIS FONOLOGIS DAN SEMANTIK) - Ruwaida Hudatullah; Suparmanto Suparmanto; Adi Rimbun Kusuma Negara (The Center for Language Development, Mataram State Islamic University., 2024)
Language is a sound system used by ethnic groups in expressing their desires with the applicable rules. The use of Sasak loanwords from Arabic through written and spoken language causes a change in writing in the Sasak language loanwords from Arabic. This causes a change in the form of the Arabic loanword into the Sasak language, because these two languages are two different languages. These changes can occur in phonological and morphological patterns. The two languages in the realm of morphology have different sequences and syllables in the occurrence of word formation, so there is a change in word class from the previous word class in syllables. Likewise at the phonological level, namely in the field of phonemes, both languages have their own rules. The entry of Islam in the Sasak lands became a determining factor for the Arabic language until it was heard by the Sasak people. The fact that the Qur'an as the foundation and source of Islamic law has made Arabic known as the Islamic language, until the implementation of worship, both obligatory and sunnah prayers using Arabic. With the close relationship between Islam and Arabic, where Islam spreads, Arabic is also starting to be known and used by the local community.